Geddes A. Think Twice, It’s All Right: Animalism, Disunity and the Self / trans. from Engl. V. A. Sermaksheva - V. A. Sermaksheva (Омский научный вестник: Серия "Общество. История. Современность")
According to animalism, each of us is numerically identical to a human animal. Disunity cases – cases in which a human animal lacks some form of mental unity – are often thought to pose a problem for animalism. Tim Bayne has recently offered some novel arguments against animalism based on one particular disunity case, namely Cerberus: a single animal with two heads, each housing its own stream of consciousness. I show that Bayne’s arguments are flawed, and that animalism is capable of handling the case.